2009
DOI: 10.1002/ddr.20342
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid in cancer and mitochondrial disease

Abstract: Cancer and the mitochondrial diseases are disparate disorders that have in common a failure of normal cellular respiratory activity in disease-affected tissues. In mitochondrial diseases, the impairment in the mitochondria is often the result of abnormalities in their mtDNA, whereas in cancerous cells, the altered respiration is driven by the Warburg effect. The oxidation of glucose (as pyruvate in the mitochondria) is inhibited and energy production relies on cytoplasmic glycolysis. This suppressed mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 145 publications
1
28
0
Order By: Relevance
“…Conversely, PMX-500FI localizes to the mitochondrial matrix using the body's carnitineacylcarnitine transport machinery [Steliou et al, 2009;El-Hattab and Scaglia, 2015]. There, it is recognized as a natural constituent and operated on in biochemical processes by mitochondrial enzymes [Steliou et al, 2009;Parameshwaran et al, 2010] that can amplify the short-lived anti-aging effects observed with AAM [Liu et al, 2002a,b;Shenk et al, 2009;Ames, 2010].…”
Section: Synthetic Carnitine Esters (Carnitinoids)mentioning
confidence: 96%
See 3 more Smart Citations
“…Conversely, PMX-500FI localizes to the mitochondrial matrix using the body's carnitineacylcarnitine transport machinery [Steliou et al, 2009;El-Hattab and Scaglia, 2015]. There, it is recognized as a natural constituent and operated on in biochemical processes by mitochondrial enzymes [Steliou et al, 2009;Parameshwaran et al, 2010] that can amplify the short-lived anti-aging effects observed with AAM [Liu et al, 2002a,b;Shenk et al, 2009;Ames, 2010].…”
Section: Synthetic Carnitine Esters (Carnitinoids)mentioning
confidence: 96%
“…It has poor pharmacokinetic properties (short half-life and first-pass hepatic clearance) and multigram doses are needed to achieve therapeutic concentrations in vivo Moos et al, 2016]. However, when butyrate and other SCFAs, including lipoic acid, present as acylcarnitine esters [Knoop, 1904;Bieber et al, 1982;Bieber, 1988;Nałezcz et al, 2004;Houten and Wanders, 2010], the body's natural carnitine-acylcarnitine transport machinery actively delivers the ester into cells, an effect that substantially increases the bioavailability of the corresponding acyl-CoA [Chenault et al, 1988;Billhardt et al, 1989;Srinivas et al, 2007;Gong et al, 2008;Piermatti et al, 2008;Rosca et al, 2009;Steliou et al, 2009Steliou et al, , 2012Parameshwaran et al, 2010Parameshwaran et al, , 2012.…”
Section: Apoptotic Priming In Mitochondriamentioning
confidence: 98%
See 2 more Smart Citations
“…12 In addition, we have synthesized a novel compound, PMX-500F, which is a lipoylcarnitine derivative. 13 In the current study, we tested whether chronic infusion of D-galactose would impair motor coordination, locomotor activity, and spatial reference memory. We also tested the effects of Lcarnitine, a-lipoic acid, and PMX-500F on control and Dgalactose-treated mice.…”
mentioning
confidence: 99%